SANKSI KODE ETIK DI KEPOLISIAN TERHADAP ANGGOTA POLRI YANG TERLIBAT PENYALAHGUNAAN NARKOTIKA - Hasanuddin Hasanuddin*; Indianto Indianto (Jurnal Tengkhiang, 2022)
Illegal circulation of narcotics and narcotics precursors, referring to Article 1 paragraph (6), Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, it is further explained that deviations in the behavior of police officers are a violation of the disciplinary regulations for members of the Indonesian National Police as regulated in government regulations of the Republic Indonesia Number 2 of 2003 concerning Disciplinary Regulations for Police Members. The trial process for the police code of ethics, if proven true, is to abuse Narcotics. This study aims to find out the process of hearing the professional code of ethics in the police against members of the police who commit criminal acts of narcotics abuse and the obstacles encountered during the process of examining members of the National Police who are involved in narcotics crimes. This study uses normative research methods supported by field research. Based on the results of this study, it has been established that investigators should keep detailed records of their investigations and that personnel problems, lack of funds, and terror-related investigators' fear are the three most common factors that impede the successful investigation of narcotics-related crimes.